Letter (copy) : Food for Spain - Tewson, Vincent
032-0180-001 International. HVT/EAB/AT/316 12th December, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue D'Orsay, Paris, VIIe. Dear Comrade Schevenels, FOOD FOR SPAIN I desire to inform you that we have arranged with the Co-operative Wholesale Society to send a further shipment of food to Barcelona. This shipment is being despatched from Liverpool today and has been consigned to Sr. Santiago, Fondo Internacional de Solidaridad, Aragon 300, Barcelona. The shipment comprises: 50 tons Dried Cod, 20 " Carbolic Soap 40 " Pale Yellow Soap 3 " Ships' Biscuits 40 25-gallon drums B.P. Cod Liver Oil. Perhaps you will be good enough to advise our comrades in Spain, accordingly. Yours sincerely, Assistant Secretary. 292/946/32/180